Differentiated of Batik Dyes and Environmental Effect in The Centre of Batik in Tasikmalaya City and Regency - Frista Mutiara; Diana Hernawati; Vita Meylani (Universitas Diponegoro, 2022)
The most extensive textile export product and one of the nation's cultural legacies is batik cloth. However, regarding environmental quality, West Java's growing demand for batik production results in garbage contaminating the nearby waterways. The type of dye is where the harmful properties of batik waste originate. With descriptive qualitative methodologies and the Miles and Huberman model, this study intends to explain the various types of dyes used by SMEs producing batik in the batik centre region of the City and Tasikmalaya Regency and their impact for environmental health. The findings revealed that small and medium-sized enterprises (SMEs) engaged in the batik industry in Tasikmalaya City (Cipedes) utilized synthetic dyes such as indigosol, reactive Procion and Remazol, dispersion, and direct (mostly monoazo and diazo). In the meantime, batik artisans at the Tasikmalaya Batik Center (also known as Sukapura batik in Sukaraja) work with reactive Procion and Remazol (diazo), indigosol, jolawe fruit peel (Terminalia bellirica), soga jambal bark (Peltophorum pterocarpum), and tingi as natural dyes (Ceriops condolleana). The impact of used the different azo dyes can change the level of pH extremely, also improve the level of BOD, COD, TDS, and heavy metal such as chromium hexavalent ((Cr(VI)) in the waters